PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN INDUSTRI TEKSTIL DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA - SUTRIA ALIMA; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research is was conducted to test effect of capital structure to profitability in industry of textile and garment company listed at indonesian stock exchange. Which is indicated by the capital structure of Debt to Equity Ratio (DER) and profitability as indicated by Return On Equity (ROE). The research population is the industry of textile and garment companies listed on the indonesian stock exchange during the period 2008-2012. In financial statements include the value of financial ratios examined included DER and ROE. Which have fluctuated during financial statement period 2008-2012. Obtained a total sample of 30 financial statements obtained throught sampling technique is purposive sampling.Analytical techniques data used is simple regresi linier and hipotesis test used t-statistics, to relationship test by correlation, and kooefecience determination to determine the effect of DER toward ROE by using SPSS program.The result of the analysis indicate that DER significant negative effect on ROE industry of textile and garment companies listed on the indonesian stock exchange period 2008-2012. At level of significance is less than 5% (0,000%). DER contribution to ROE is 66%, as indicated by the R-square of 66%, while the remaining 44%, are influenced by other factors not included in the research model.Key words: Debt to Equity Ratio (DER) and Return On Equity (ROE)